2014
DOI: 10.1369/0022155414538821
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistological Insight into the Correlation between Neuropilin-1 and Epithelial-Mesenchymal Transition Markers in Epithelial Ovarian Cancer

Abstract: The mechanism by which neuropilin-1 (NRP-1) induces malignancy in Epithelial Ovarian Cancer (EOC) is still unknown. This study is the first to demonstrate the relationship between NRP-1 expression and EMT markers vimentin, N-cadherin, E-cadherin and Slug. We used tissue microarrays containing the three main subtypes of EOC tumors: serous, mucinous cystadenocarcinoma and endometrioid adenocarcinoma and representative cases retrieved from our pathology archives. Immunohistochemistry was performed to detect the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 68 publications
4
17
0
Order By: Relevance
“…Regarding moderately differentiated SCC we observed high (9 cases, 56.3%) and low expression (7 cases, 43.8%). Many previous studies on OSCCs, ovarian cancer, tongue SCCs [4,37,39] reported similar finding.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Regarding moderately differentiated SCC we observed high (9 cases, 56.3%) and low expression (7 cases, 43.8%). Many previous studies on OSCCs, ovarian cancer, tongue SCCs [4,37,39] reported similar finding.…”
Section: Discussionsupporting
confidence: 74%
“…[49] Sirin et al had observed similar finding in ovarian carcinoma as N-cadherin had no significant relationship with tumor grade. [39] N-cadherin expression was significantly related to tumor stage (p < .05) as 69.4% of HNSCCs with advanced TNM stage demonstrated high expression of N-cadherin. Similar to our finding was observed by Sirin et al [39] in ovarian cancer, Krisanaprakornkit et al [37] in tongue SCCs, Domenico et al in OSCCs.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Additionally, numerous transcriptional regulators act downstream of NRP-1 such as SNAI1 17 , a transcriptional repressor pivotal for cell differentiation and survival that reverses the tumor suppressive effects induced by TGFβ1 in early stage breast cancer 18 . In a previous study on ovarian cancer we showed that NRP-1 had a positive relation to EMT markers 19 .…”
Section: Introductionmentioning
confidence: 82%
“…Furthermore, PDAC is characterized by aberrant expression of NRP-1 [45, 60, 61], often correlated with tumor progression and poor patient prognosis [62]. Interestingly, recent evidences have implicated a novel regulatory role of NRP-1 in epithelial-to-mesenchymal transition (EMT); an evolutionary conserved developmental process, which is evoked during tumor invasion and metastasis of several cancers [63, 64]. Similarly, recent studies suggest that endothelial-to-mesenchymal transition (EndMT), which is originally observed during heart development, has a major role in pathological settings of cancer and fibrosis [2125, 31].…”
Section: Introductionmentioning
confidence: 99%